Pengaruh Pemberian Platelet-Rich Plasma Terhadap Derajat Keparahan Psoriasis Vulgaris - Nanda Earlia; Cut Yunita; Mikyal Bulqiah; Aqil Yuniawan Tasrif; Karamina Maghfirah (LITBANG RSUDZA, 2022)
Psoriasis vulgaris is an autoimmune disease that is influenced by multifactor, namely environmental, genetic (HLA-Cw6), and immune system dysregulation (IL-17 or IL-22), resulting in increased proliferation of keratinosit in the epidermis. Histologically characterized by parakeratosis, hyperkeratosis, elongated rete ridge, Monro micro abscess, and Kogoj micro abscess. The clinical picture is red patches with thick scales, especially in the trauma area. Platelet Rich Plasma (PRP) is an autologous preparation of platelets that strengthens in plasma and is a powerful anti-inflammatory agent. The immunomodulatory and anti-inflammatory effects of PRP are believed to play a role in the treatment of chronic inflammation patients. One of the important mediators in the pathogenesis of psoriasis is nuclear factor kappa B (NF-κB) and PRP exerting an inhibitory effect on NF-κB. The aim of the study was to assess the effect of PRP on the severity and quality of life of psoriasis vulgaris patients. The design of this study is a paired numerical comparative analysis using two groups with two measurements. The research design was a randomized, undisguised clinical trial and a parallel design. The study lasted for 6 weeks. Sampling was done by total sampling involving 20 psoriasis Vulgaris patients, then divided into two groups: intervention group and control group. The test group received 2 PRP injections and topical combination therapy (salicylic acid 3% + Vaseline album cream), while the control group only received topical combination therapy. The results of this study found a decrease in PASI and DLQI scores in the intervention group compared to the control group (p<0.005). This study concludes that the administration of PRP can reduce the severity of psoriasis Vulgaris as well as improve the quality of life of psoriasis Vulgaris patients.